Development of a Mobile Robot with Camera-based Target Tracking and Obstacle Avoidance Systems - Mohamad Jamatolail, Mohamed Fitri; Ambar, Radzi; Abd Wahab, Mohd Helmy; Isa, Khalid; Abdul Kadir, Herdawatie; Ahmad, Muhammad Shukri; Abd Jamil, Muhammad Mahadi; Mohammadian, Masoud (International Journal of Integrated Engineering, 2020)
This work describes the preliminary design and development of a mobile robot called CREC (Camera-Based Mobile Robot for Elderly Care). The robot uses a low-cost HC-SR04 ultrasonic sensor to avoid obstacle, and a Pixy CMUcam5 camera as the vision-based sensor to track the target. This camera uses colour marker tag to follow and monitor the target. CREC uses an Arduino UNO microcontroller to fuse data conveyed by the ultrasonic sensor and camera so that the robot can follow the target and avoid obstacles simultaneously. In this work, the hardware design of CREC is described. Furthermore, preliminary experiments to characterize the ultrasonic sensor and Pixy camera are demonstrated to verify the usefulness of the selected sensors for the mobile robot.